HISTORY OF DEVELOPMENT OF THE NATIONAL WRESTLING SPORT (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article provides a comprehensive overview of the history and development of wrestling in Uzbekistan, tracing its origins from ancient times to the modern era. It explores the cultural significance of wrestling in Uzbek society, the influence of the Soviet era, and the revival of traditional wrestling post-independence. The document highlights key milestones, prominent wrestlers, and government initiatives that have shaped the sport. Additionally, it covers recent developments, including grassroots programs, women's wrestling, and international successes, showcasing Uzbekistan's ongoing commitment to preserving and promoting its wrestling heritage.